2009
DOI: 10.1002/pola.23256
|View full text |Cite
|
Sign up to set email alerts
|

Functional colloidal particles stabilized by layered silicate with hydrophilic face and hydrophobic polymer brushes

Abstract: In this study, we describe a new strategy for producing narrowly dispersed functional colloidal particles stabilized by a nanocomposite with hydrophilic clay faces and hydrophobic polystyrene (PS) brushes on the edges. This method involves preparation of polymer brushes on the edges of clay layers and Pickering suspension polymerization of styrene in the presence of the nanocomposites. PS brushes on the edges of clay layers were prepared by atom transfer radical polymerization. X-ray diffraction and thermograv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…Pickering emulsion droplets are also used as versatile polymerization vessels to fabricate hybrid polymer spheres and capsules with supracolloidal structures [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. The solid particles first self-assemble at the liquid-liquid interface and act as effective stabilizers during the polymerization process, eliminating the need for any conventional stabilizers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pickering emulsion droplets are also used as versatile polymerization vessels to fabricate hybrid polymer spheres and capsules with supracolloidal structures [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. The solid particles first self-assemble at the liquid-liquid interface and act as effective stabilizers during the polymerization process, eliminating the need for any conventional stabilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Such a surfactant-free emulsion polymerization process, called Pickering emulsion polymerization, is more attractive for preparation of hybrid beads than the conventional emulsion polymerization method. Polymerizations based on Pickering emulsion include Pickering miniemulsion polymerization, Pickering suspension polymerization, Pickering dispersion polymerization and Pickering emulsion interface-initiated atom transfer radical polymerization (PEII-ATRP) [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Magnetic microparticles with poly(methyl methacrylate) (PMMA) [35] or polyaniline (PANI) [44] cores and Fe 3 O 4 nanoparticle shells have been prepared by Pickering suspension polymerization; polystyrene (PS)-Fe 3 O 4 microparticles have been produced by Pickering dispersion polymerization [36].…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Wu and coworkers anchored ATRP initiator to the edges of clay particles, and prepared PS brushes on the edges of clay particles by ATRP (Figure 3.7). 35 The clay particles with hydrophilic faces and hydrophobic PS brushes on the edges can be used as efficient stabilizers in Pickering suspension polymerization of styrene. Figures 3.8a and b show TEM images of PS colloidal particles.…”
Section: Clay Layers With Hydrophilic Faces and Hydrophobic Ps Brushementioning
confidence: 99%
“…Pickering emulsion/suspension polymerization has been proven as a fascinating method to fabricate polymer microspheres or polymer/inorganic nanocomposite microspheres [1][2][3][4][5][6][7][8][9][10][11][12]. It has been found that the size and morphology of polymer microspheres prepared by Pickering emulsion polymerization are highly depended on the surface structures of the solid particles [13,14].…”
Section: Introductionmentioning
confidence: 99%